ANALYSIS OF THE IMPACT OF WATER QUALITY DECLINE AND TERRESTRIAL BIOTA DISTURBANCE DUE TO GALENA ORE MINING ACTIVITIES: A CASE STUDY OF PT CHRISTINA EXPLO MINING - Amran, Amran; Sibali, Alwi (MSJ : Majority Science Journal, 2025)
This study aims to evaluate the environmental impacts of galena ore mining activities, particularly related to water quality degradation and disturbances to terrestrial biota. This study was conducted in the operational area of ​​PT Christina Explo Mining in 2024, focusing on the water quality of the Sasak and Rero rivers and disturbances to flora and fauna due to land clearing activities. The methods used included sampling surface water and clean water in the mining area and observing terrestrial biota. The analysis results indicate that water quality in the study area remains within the quality standards based on Government Regulation No. 22 of 2021 and Minister of Health Regulation No. 2 of 2023. However, potential disturbances to terrestrial biota habitats were identified, necessitating sustainable environmental management and regular monitoring